SCORING METRIC FOR PHYSICAL ACTIVITY PERFORMANCE AND TRAINING - JUHAS, Brett; SUR, Sudipto (2022)
Certain aspects of the present disclosure provide a method for assessing the performance of a physical activity, including: recording motion capture data while a training subject demonstrates a physical activity sequence; identifying one or more primary body elements based on the motion capture data; deriving one or more path characteristic metrics based on a state variable set and the one or more primary body elements, wherein the state variable set defines the state of a body at any given time; and defining an ideal activity path of the physical activity sequence based on the one or more path characteristic metrics.